Radar imaging of the ocean waves - Kanevskii, M. B. (Mikhail Borisovich) (Elsevier, 2009)
This book is dedicated to studying the ocean with radar tools, in particular, with space radars. Being intended mainly for the scientists preoccupied with the problem (as well as senior course students), it concentrates and generalizes the knowledge scattered over specialized journals. The significant part of the book contains the results obtained by the author. Systematically collects and describes the approaches used by different laboratories and institutions. Deals with the physics of radar imagery and specifically with ocean surface imagery. Useful for students and researchers specializing in the area of ocean remote sensing using airborne or space-borne radars, both SAR and RAR.